2022
DOI: 10.54536/ajec.v1i2.568
|View full text |Cite
|
Sign up to set email alerts
|

The Threats of Climate Change on Water and Food Security in South Africa

Abstract: Globally, water and food crises are exacerbated by climate change, population growth and changing lifestyles. These phenomena have resulted in escalating cycles of civil unrest and conflicts.  In South Africa, climate change has led to increased temperatures resulting in numerous deadly heat waves and varying rainfall patterns contributing to deadly flooding in most provinces and droughts in others. These extreme climatic conditions significantly impact agricultural production and water insecurity nationally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We established that weak institutional coordination has significantly hindered climate change governance at the country's national and local levels. This outcome is also expressed by Adom et al (2022), that the unconnected climate change issue into key sectors of the economy, such as trade and industry, water and agriculture, have contributed to a weak understanding of the threat of climate change on livelihoods and is an abstract concept to communities. Strengthening institution coordination by coherently connecting sectoral objectives and coordinating climate change activities between national and local levels will ensure climate change actions are effectively implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We established that weak institutional coordination has significantly hindered climate change governance at the country's national and local levels. This outcome is also expressed by Adom et al (2022), that the unconnected climate change issue into key sectors of the economy, such as trade and industry, water and agriculture, have contributed to a weak understanding of the threat of climate change on livelihoods and is an abstract concept to communities. Strengthening institution coordination by coherently connecting sectoral objectives and coordinating climate change activities between national and local levels will ensure climate change actions are effectively implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Given these governance failures, South Africa has been exposed to adverse impacts of climate change in water provision, food production, massive unemployment, outbreak of communicable diseases and threats to a sustainable livelihood (Adom et al, 2022). The increased heat stress as a result of climate change has affected crop productivity, leading to hunger and starvation (Masipa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts the assertion Butts (1997) who affirmed that the combination of population growth, rising water consumption, improvements in public health and welfare, rapid urbanization causing problems like contamination of raw water resources, widely spread land sealing with prevention of natural groundwater recharge, and the impacts of global climate change, will undoubtedly lead to more pressure on politicians and industry to resolve water problem. Global climate change, population increase, and lifestyle changes all worsen the water and food challenges (Richard Kwame et al, 2022). Results also showed that hotels/resorts in White Beach, Puerto Galera neglect to support locals through buying products from local people which connotes that the hotels do not typically buy products from the local people of the host community.…”
Section: Resultsmentioning
confidence: 99%
“…Although food security at household and national levels is interrelated, more often the observations are that the two metrics are not always in tandem, to the extent that national level food security does not guarantee household level food security (Altman et al, 2009;Drysdale et al, 2019;Adeniyi et al, 2021;Adom et al, 2022). Food security has been identified in various literature to be a crucial issue needing attention at household level for many African countries (Crush and Frayne, 2010), especially in the wake of high food prices and climate change impacts on agricultural productivity (Lobell and Gourdji, 2012).…”
Section: Introductionmentioning
confidence: 99%